Application of Artificial Intelligence Models for Evapotranspiration Prediction along the Southern Coast of Turkey. (24th August 2021) - Hameed, Mohammed Majeed; AlOmar, Mohamed Khalid; Mohd Razali, Siti Fatin; Kareem Khalaf, Mohammed Abd; Baniya, Wajdi Jaber; Sharafati, Ahmad; AlSaadi, Mohammed Abdulhakim
Abstract : Reference evapotranspiration ET o   is one of the most significant factors in the hydrological cycle since it has a great influence on water resource planning and management, agriculture and irrigation management, and other processes in the hydrological sector. In this study, an efficient and local predictive model was established to forecast the monthly mean ET o   t over Turkey based on the data collected from 35 locations. For this purpose, twenty input combinations including hydrological and geographical parameters were introduced to three different approaches called multiple linear regression MLR, random forest RF, and extreme learning machine ELM . Moreover, in this study, large investigation was done, involving the establishment of 60 models and their assessment using ten statistical measures. The outcome of this study revealed that the ELM approach achieved high accurate estimation in accordance with the Penman–Monteith formula as compared to other models such as MLR and RF . Moreover, among the 10 statistical measures, the uncertainty at 95% U 95 indicator showed an excellent ability to select the best and most efficient forecast model. The superiority of ELM in the prediction of mean monthly ET o   over MLR and RF approaches is illustrated in the reduction of the U 95 parameter to 49.02% and 34.07% for RF and MLR models, respectively. Furthermore, it is possible to develop a local predictive model with the help of computer to estimate the ET o   using the simplest and cheapest meteorological and geographical variables with acceptable accuracy.